Strategic management : - Pitts, Robert A. (Thomson/South-Western, 2006)
Strategic management: Building and sustaining competitive advantage shows you in detail how the world's top companies build, extend, and sustain a competitive advantage. How do they do it? Through distinctive competence, quality, globalization, change, and ethics. And because this business textbook is rich with study tools, Strategic management: Building and sustaining competitive advantage gives you the competitive advantage on the test as well!